2020
DOI: 10.3390/jcm9051382
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal Echocardiography as a Monitoring Tool during Transvenous Lead Extraction—Does It Improve Procedure Effectiveness?

Abstract: Background: Transesophageal echocardiography (TEE) is a valuable tool for monitoring the patient during transvenous lead extraction (TLE), but the direct impact of TEE on the effectiveness and safety of TLE has not yet been documented. Methods: The effectiveness of TLE and short-term survival were compared between two groups of patients: 2106 patients in whom TEE was performed before and after TLE and 1079 individuals in whom continuous TEE monitoring was used. The procedure-related risk of major complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 22 publications
(42 reference statements)
0
54
1
Order By: Relevance
“…The results of our study for the first time confirmed higher procedural efficacy of transvenous lead extraction and reduced risk of cardiovascular injury during TLE under TEE guidance. The study also showed that continuous TEE monitoring helped achieve 100% periprocedural survival [17,18].…”
Section: Importance Of Intraprocedural Tee For Safety and Effectivenementioning
confidence: 84%
See 4 more Smart Citations
“…The results of our study for the first time confirmed higher procedural efficacy of transvenous lead extraction and reduced risk of cardiovascular injury during TLE under TEE guidance. The study also showed that continuous TEE monitoring helped achieve 100% periprocedural survival [17,18].…”
Section: Importance Of Intraprocedural Tee For Safety and Effectivenementioning
confidence: 84%
“…Assessment of the dynamics of bleeding helps the operator make an extremely important decision whether a chest drain is required, or whether it is enough to monitor the patient if the bleeding stops. In an emergency situation usually there is no time for inserting an esophageal probe and starting diagnostic imaging [12][13][14][15][16][17][18].…”
Section: Transvenous Lead Extraction Proceduresmentioning
confidence: 99%
See 3 more Smart Citations